"Azole" as privileged heterocycle for targeting the inducible cyclooxygenase enzyme. Issue 2 (2nd November 2020) - Prasher, Parteek; Sharma, Mousmee
Abstract: An over‐expression of COX‐2 isoenzyme belonging to the Cyclooxygenase Enzyme Family triggers the overproduction of pro‐inflammatory prostaglandins that instigate the development of chronic inflammation and related disorders. Hence, the rationally designed drugs for mitigating over‐activity of COX‐2 isoenzyme play a regulatory role toward the alleviation of the progression of these disorders. However, a selective COX‐2 inhibition chemotherapy prompts several side effects that necessitate the identification of novel molecular scaffolds for deliberating state‐of‐the‐art drug designing strategies. The heterocyclic "azole" scaffold, being polar and hydrophilic, possesses remarkable physicochemical advantages for designing physiologically active molecules capable of interacting with a wide range of biological components, including enzymes, peptides, and metabolites. The substituted derivatives of azole nuclei enable a comprehensive SAR analysis for the appraisal of bioactive profile of the deliberated molecules for obtaining the rationally designed compounds with prominent activities. The comprehensive SAR analysis readily prompted the identification of Y‐shaped molecules and the eminence of bulkier group for COX‐2 selective inhibition. This review presents an epigrammatic collation of the pharmacophore‐profile of the chemotherapeutics based on azole motif for a selective targeting of the COX‐2 isoenzyme.